Advent of 2D Rhenium Disulfide (ReS2): Fundamentals to Applications. (30th January 2017) - Rahman, Mohammad; Davey, Kenneth; Qiao, Shi‐Zhang
Abstract : Rhenium disulfide (ReS2 ) is a two‐dimensional (2D) group VII transition metal dichalcogenide (TMD). It is attributed with structural and vibrational anisotropy, layer‐independent electrical and optical properties, and metal‐free magnetism properties. These properties are unusual compared with more widely used group VI‐TMDs, e.g., MoS2, MoSe2, WS2 and WSe2 . Consequently, it has attracted significant interest in recent years and is now being used for a variety of applications including solid state electronics, catalysis, and, energy harvesting and energy storage. It is anticipated that ReS2 has the potential to be equally used in parallel with isotropic TMDs from group VI for all known applications and beyond. Therefore, a review on ReS2 is very timely. In this first review on ReS2, we critically analyze the available synthesis procedures and their pros/cons, atomic structure and lattice symmetry, crystal structure, and growth mechanisms with an insight into the orientation and architecture of domain and grain boundaries, decoupling of structural and vibrational properties, anisotropic electrical, optical, and magnetic properties impacted by crystal imperfections, doping and adatoms adsorptions, and contemporary applications in different areas. Abstract : ReS2 is reviewed comprehensively for the first time, including the state‐of‐the‐art progress and prospects of the synthesis, fundamental properties, and applications.